Multidimensional Outcome Parameters in a Cress Seedling—CuCl2 Crystallization Assay to Corroborate Specific Effects of Stannum metallicum 30x Compared to Lactose 30x - Doesburg, Paul; Andersen, Jens-Otto; Scherr, Claudia; Kokornaczyk, Maria Olga; Baumgartner, Stephan (Homeopathy, 2024)
Background Previously we developed a test system which yielded highly significant evidence for specific effects of a Stannum metallicum 30x preparation in a multi-center replication trial. This test system is based on cress seed germination in homeopathic or control samples, CuCl2 crystallization of the cress extract, and subsequent digital textural image analysis of the resulting crystallization patterns.Objectives The current study aimed to investigate whether three novel outcome parameters could further corroborate and possibly characterize the specific effects of Stannum metallicum 30x.Methods To this end, (1) cress seedling length, (2) a second texture analysis parameter, entropy and (3) the local connected fractal dimension (LCFD) of crystallization patterns as a measure of complexity were considered. The stability of the experimental setup was monitored throughout the entire investigation with systematic negative control (SNC) experiments.Results Cress length and entropy revealed a time-modulated potency treatment effect, in the absence of a significant main treatment effect. This indicated that the effect of the potency treatment varied significantly across the different experimental days. LCFD yielded a highly significant potency treatment effect. In addition, a significant interaction of treatment with experimental day seems to indicate a modulation of this effect. No significant effects were observed in any of the evaluations of the SNC experiments, indicative of a stable experimental setup and a reliable and specific treatment effect. Neither significant nor strong correlations were found between the four parameters, indicating that they reflect different effects of Stannum metallicum 30x on the organism treated.Conclusion This quadruple characterization of the biological effects of Stannum metallicum 30x provides an unprecedented opportunity for basic homeopathy research into, among others, the presumed specificity of homeopathic preparations.
Keywords: CuCl2 crystallization; fractal dimension; bio-assay; systematic negative control experiments; potentized substances